Dynamic of dominance, growth and bromatology of Eragrostis plana Nees in secondary vegetation area - Scheffer-Basso, Simone; Cecchin, Kalinca; Favaretto, Adriana (Revista Ciência Agronômica, 2016)
The objective of this work was to evaluate the dominance, growth and bromatology of tough lovegrass or ‘annoni’ grass (Eragrostis plana) in secondary vegetation area. The evaluations were carried out at 23, 45, 64, 86, 111, 132, 153, and 174 days of growth after a mowing. The tough lovegrass was the dominant species on the area, accounting for 76 to 90% of biomass. There was a linear increase for leaf (9.8 kg DM ha-1 day-1) and total dry mass (16.9 kg DM ha-1 day-1) of the tough lovegrass. During the 111 days of the vegetative stage, the biomass was composed only of leaves, and the flowering started at 132 days. At 174 days, the tough lovegrass accumulated about 4,000 kg DM ha-1, 650 kg DM ha-1 of which was composed of inflorescences. The growth analysis revealed a specific leaf area of 72 cm2 g-1 and a maximum leaf area index of 2.1. The leaf area ratio decreased from 72.2 to 43.9 cm² g-1 between the 23rd and 174th days. The bromatological analysis showed a high content of neutral detergent fiber (85.3-90.4%) and acid detergent fiber (39.4-42.8%), as well as low crude protein content (3.9-9.9%), indicating the low forage quality of the species.